Attempt to estimate the symmetry of trunk with regard to functioning of student’s limbs at the medical academy in Poznań - Losiak, Barbara (Anthropological Review, 1974)
To trace the asymmetry in the trunk formation of students (50 males and 50 females) the following measurements were carried out: the breadth and half-girth of the right and left shoulder, half-girth of the right and left side of chest and half-girth of both hips. The results of research show a distinct asymmetry in the shape of the trunk (table 1 and 2). Te major part of subjects (about 60%) is characterized by greater dimensions of the right shoulder and the right side of chest which is without doubt he results of functional asymmetry in the upper limb (right-handedness). Asymmetry in the build of the hip-girdle is a common occurrence. No distinct prevalence however can observed in the frequency of occurring of oue of asymmetry types and that is probably connected with small functional differentiation in the lower limbs.